2016
DOI: 10.18632/oncotarget.13402
|View full text |Cite
|
Sign up to set email alerts
|

Association of multiple genetic variants with breast cancer susceptibility in the Han Chinese population

Abstract: We selected 13 tag single nucleotide polymorphisms (tSNPs) to investigate whether they were associated with breast cancer risk in the Chinese Han population. Upon statistical analyses of clinical data from 551 patients and 577 controls, we found that six of the 13 SNPs were associated with breast cancer; namely, rs4973768(Odds ratio (OR) = 1.30, 95% confidence interval (CI) =1.01-1.67), rs981782(OR =1.30, 95% CI=1.01-1.66), rs1432679(OR =0.84, 95% CI=0.70-0.99), rs10759243(OR=1.30, 95%CI=1.09-1.55), rs10822013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…However, numerous investigations point to the contradictory effects of H19 on tumor development, progression, and treatment [16,17,18,19,20], and indicate the complexity of H19 functionality. In addition, polymorphisms within the H19 gene in many ethnic populations have been related to the susceptibility to various tumor types, including bladder [21,22], gastric [23], colorectal [24], lung [25], breast [26,27,28], ovarian [29,30], liver [31], bone [32], and oral cancer [33]. Nevertheless, these results provide no consensus regarding the promotive or protective effect of individual H19 SNPs on cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…However, numerous investigations point to the contradictory effects of H19 on tumor development, progression, and treatment [16,17,18,19,20], and indicate the complexity of H19 functionality. In addition, polymorphisms within the H19 gene in many ethnic populations have been related to the susceptibility to various tumor types, including bladder [21,22], gastric [23], colorectal [24], lung [25], breast [26,27,28], ovarian [29,30], liver [31], bone [32], and oral cancer [33]. Nevertheless, these results provide no consensus regarding the promotive or protective effect of individual H19 SNPs on cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…The association between these SNPs and cancer risk has been studied, while evidence of rs3024270 GG genotype and cancer risk are relatively limited. A study by Li et al [20] reported an increased risk of colorectal cancer in a Chinese population with the rs3024270 GG genotype. A meta-analysis conducted by Lv et al [21] investigated the association between long noncoding RNA polymorphisms and cancer risk, and the rs3024270 C>G polymorphism was reported to be correlated with an overall cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…However, another study found a decreased risk of invasive bladder cancer in patients with the rs3024270 CC genotype in the Chinese population [41]. Besides the rs3024270 C>G polymorphism, a series of studies reported the role of the rs2839698 G>A polymorphism in platinum-based chemotherapy response in lung cancer [42], colorectal cancer [20], gastric cancer [24] and rheumatoid arthritis [22]. The rs217727 G>A polymorphism was also reported to be associated with a risk of oral squamous cell carcinoma [19], osteosarcoma [43], bladder cancer [44], cervical cancer of the squamous carcinomas subtype [20], and breast cancer [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations